A Study on the Visual Elements of Shadow Puppets in Southwest China - Cheng, Xiaochun; Musdi, Shanat (Aliva Global Research and Development, 2021)
This paper focuses on the shadow puppets in Southwest China, as one of the principal styles of Chinese shadow play and has been a popular local performing art and storytelling tradition. The Chinese shadow play is beautifully crafted, and the design follows traditional moral evaluation and aesthetics. Thus, the main objective of this study is to understand the visual elements and aesthetic characteristics of the shadow puppet characters, and how the socio-cultural background influeances them. Scholars have less explored shadow puppets in the visual realms. The study employed a qualitative descriptive method based on iconography theory. The researcher had collected and studied samples and generalizes the cultural causes and visual characteristics. Therefore, this research will contribute to providing more insight into the aesthetic world of shadow puppets and give inspire towards modern art and design industry. It also delivers as a symbol of cultural identity and loyalty among the young generation.